PENGARUH PERMAINAN DOMINO TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN ANAK USIA 5-6 TAHUN DI TK DARUSSALAMAH KECAMATAN TAPUNG KABUPATEN KAMPAR - Arfany, Dede; Risma, Devi; Solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of the game of dominoes towards the ability to know the concept of number of children aged 5-6 years in TK Darussalamah in sub district Tapung district of Kampar. The research used experimental method with one group pre-test post-test design. The sample used in this study were 15 students. The data collection technique used is observation. Technique of data analysis using t-test test by using program of SPSS 20. Research hypothesis that there is the effect of the game of dominoes towards the ability to know the concept of number of children aged 5-6 years in TK Darussalamah in sub district Tapung district of Kampar. Based on data analysis known tcalculated = 23,883 > ttable = 2,145 with Sig. (2-tailed) = 0.000. Because Sig <0,05 it can be concluded that there are differences in the ability to recognize the concept of numbers before and after the domines game. It can be interpreted that there is the effect of the game of dominoes towards the ability to know the concept of number of children aged 5-6 years in TK Darussalamah in sub district Tapung district of Kampar significant as much as 61.25%.Keyword: Ability to know the concept of numbers, Game of dominoes